Method for manufacturing conductive material having larger specific surface area and structure thereof

JP2025031470AActive Publication Date: 2025-03-07TALENT HUB INVESTMENT CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024012144
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2024-01-30
Publication Date
2025-03-07
Estimated Expiration
2044-01-30

Smart Images

  • Figure 2025031470000001_ABST
    Figure 2025031470000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a conductive material having a larger specific surface area.SOLUTION: A method includes the steps of forming a block layer on an outer surface of a support precursor (e.g., conductive nanofiber) to produce a mixed precursor, rolling the mixed precursor to crack a portion of the outer surface of the block layer to form a plurality of crack gaps, exposing a portion of the outer surface of the support precursor through the plurality of crack gaps, and adding a conductive material to the mixed precursor such that the conductive material comes into contact with and is electrically connected to the support precursor through the plurality of crack gaps, manufacturing a conductive material with a larger specific surface area.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] High surface area materials are materials with an extremely large specific surface area, and their industry is developing rapidly. The advantage of this type of material is its large ratio of surface area to volume, and it is widely used in many fields.

[0002] Industrial applications of high surface area materials include many areas such as catalysis, adsorption and energy storage.

[0003] High surface area materials often function as efficient catalysts. The large surface area provides a more active surface, which increases the rate and efficiency of reactions. Such materials have important applications in the fields of chemical synthesis, environmental protection, e.g., automobile exhaust gas purification, chemical reaction catalysis, and energy conversion, such as fuel cells.

[0004] Large surface area materials can have many fine pores and often perform well in adsorption and separation processes. For this reason, large surface area materials are widely used in fields such as gas-liquid separation, water treatment, and waste treatment. For example, activated carbon is a common large surface area adsorbent that is used to remove organic matter and heavy metal ions from water.

[0005] Large surface area materials play an important role in the field of energy storage. For example, porous materials with large surface areas are often used as electrode materials for supercapacitors and lithium-ion batteries to increase charge transfer speed and capacitance. Among these, supercapacitor technology has attracted attention.

[0006] Capacitors vary in appearance and structure, and there are many commonly used capacitors on the market. Most capacitors are made up of at least two metal plates or conductor surfaces separated by a layer of insulation. Conductors can be metal foils, films, sintered metal beads, or electrolytes. Non-conductive insulating materials can improve the energy storage capacity of a capacitor. Common insulating materials include glass, ceramics, plastic films, paper, mica, and metal oxides. Capacitors play an important role in many electronic circuits and energy storage applications.

[0007] Capacitors are widely used in electronic circuits. For energy storage, they can be used as an alternative to batteries in some applications. When high power is required, capacitors are more suitable than batteries.

[0008] Overall, as an important electronic component and power energy storage component, capacitors have the functions of storing electrical energy and adjusting circuit characteristics. From electronic devices to power systems, various types of capacitors play important roles in various applications, all of which are essential to the application of capacitors. With the continuous development of science and technology, capacitors continue to play an important role in promoting progress and innovation in the electronic field.

[0009] Ferroelectric materials with high dielectric constants in the temperature range of 25-200°C include barium titanate, lead magnesium niobate, and lead zirconate titanate. However, lead-containing materials have limited their development because they are prone to volatilization at high temperatures, react with electrodes, and are inherently toxic. Thus, barium titanate ceramics have become one of the most widely used dielectric materials for electronic ceramic capacitors today.

[0010] With the development of industry, there is an increasing need for more efficient and large surface area materials in the fields of catalysts, adsorbents and energy storage. Especially in the energy storage field, the high value-added power storage market and the power electronics equipment market are gradually becoming smaller and more powerful. Dielectric materials are being developed in the direction of high energy storage density, high charge and discharge efficiency, easy processing and molding, and stable performance. Therefore, the industry needs a method to prepare conductor materials with larger specific surface area to produce conductive materials with high specific surface area for applications in the fields of catalysts, adsorbents and energy storage as mentioned above.

[0011] In order to solve the above problems of the prior art, the present invention provides a method and structure for producing a conductive material with a larger specific surface area, the method includes the steps of forming a block layer on an outer surface of a precursor support, performing rolling to crack a part of the outer surface of the block layer to expose a part of the outer surface of the precursor support, and adding a conductive material electrically connected to the part of the precursor support to produce a conductive material with a larger specific surface area. Summary of the Invention The problem to solve

[0012] An object of the present invention is to provide a method for producing a conductive material with a larger specific surface area, the method including the steps of: forming a block layer on an outer surface of a precursor support; rolling a part of the outer surface of the block layer to crack it and expose a part of the outer surface of the precursor support; and adding a conductive material to the mixed precursor so as to be electrically connected to the part of the precursor support, thereby producing a conductive material with a larger specific surface area.

[0013] In order to achieve the above objects and effects, the present invention provides a method for producing a conductive material having a larger specific surface area, comprising the steps of forming a block layer on the outer surface of a support precursor to produce a mixed precursor, rolling the mixed precursor to crack a part of the outer surface of the block layer to form a plurality of crack gaps, exposing a part of the outer surface of the support precursor through the plurality of crack gaps, and adding a conductive material to the mixed precursor so that the conductive material contacts and is electrically connected to the support precursor through the plurality of crack gaps, thereby producing a conductive material having a larger specific surface area. By using this method, a conductive material having a larger specific surface area can be produced.

[0014] In order to achieve the above objects and effects, the present invention provides a structure of a conductive material having a larger specific surface area, comprising a substrate and a first large specific surface area conductive slurry layer. The first large specific surface area conductive slurry layer comprises a first support precursor, a first block layer, and a first plurality of particles. The first block layer covers the first support precursor. The first block layer comprises a plurality of first crack gaps. The first plurality of particles are arranged corresponding to the first crack gaps. By using this structure, a conductive material having a larger specific surface area can be provided.

[0015] According to one embodiment of the present invention, in the step of forming a block layer on the outer surface of the support precursor to produce a mixed precursor, the support precursor is added to a titanium tetrachloride solution to produce a mixed precursor and form a block layer on the outer surface of the support precursor.

[0016] According to one embodiment of the present invention, in the step of forming a block layer on the outer surface of a support precursor to produce a mixed precursor, the mixed precursor is added to a barium acetate solution, and the barium acetate in the barium acetate solution reacts with the titanium oxide in the block layer to form barium titanate.

[0017] According to one embodiment of the present invention, in the step of adding a conductive material to the mixed precursor to produce a conductive material with a larger specific surface area, the conductive material includes a polyvinyl butyral solution, a conductive gel, and barium titanate particles, so that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps. During rolling, the block layer is cracked to form a plurality of crack gaps. The conductive gel and the barium titanate particles contact and are electrically connected to the support precursor through a plurality of crack gaps, producing a conductive material with a larger specific surface area.

[0018] According to one embodiment of the present invention, after the step of adding a conductive material to the mixed precursor to produce a conductive material with a larger specific surface area, such that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps, the method further includes the steps of coating the conductive material with a larger specific surface area on the upper and lower surfaces of a substrate, heating to a sintering temperature, and forming a capacitor.

[0019] According to one embodiment of the present invention, the support precursor comprises carbon nanotubes (CNTs) or nanometric metal fibers.

[0020] According to one embodiment of the present invention, the polyvinyl butyral solution includes polyvinyl butyral (PVB) as an adhesive or solvent, toluene (C7H8), and ethanol (CH3CH2OH).

[0021] According to one embodiment of the present invention, in the step of forming a block layer on the outer surface of the support precursor to produce a mixed precursor, a hydrothermal synthesis method, an electroless plating method, an electroplating method, and a physical vapor deposition (PVD) method, a chemical vapor deposition (CVD) method, or a combination of any of the above methods is adopted to form the block layer on the outer surface of the support precursor.

[0022] According to one embodiment of the present invention, the sintering temperature is 1000°C to 1350°C.

[0023] According to one embodiment of the present invention, the structure further includes a second large surface area conductive slurry layer disposed below the substrate. The second large surface area conductive slurry layer includes a second support precursor, a second block layer, and a plurality of second particles. The second block layer covers the second support precursor. The second block layer includes a plurality of second crack gaps. The plurality of second particles are disposed corresponding to the plurality of second crack gaps.

[0024] The first substrate precursor comprises carbon nanotubes (CNTs) or nanometric metal fibers.

[0025] According to one embodiment of the present invention, the first and second blocking layers are barium titanate.

[0026] According to an embodiment of the present invention, the plurality of first particles and the plurality of second particles are metal particles. [Brief description of the drawings]

[0027] [Figure 1] 1 is a flow chart of material production according to one embodiment of the present invention. [Figure 2A] FIG. 2 is a schematic diagram of a material structure according to one embodiment of the present invention. [Figure 2B] FIG. 2 is a schematic diagram of a material structure according to one embodiment of the present invention. [Figure 2C] FIG. 2 is a schematic diagram of a material structure according to one embodiment of the present invention. [Figure 2D] FIG. 2 is a schematic diagram of a material structure according to one embodiment of the present invention. [Diagram 3] 2 is a flow chart of the manufacture of a capacitor material according to one embodiment of the present invention. [Figure 4] 2 is a flow chart of an application according to an embodiment of the present invention. [Diagram 5] 1 is a schematic diagram of a capacitor structure according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] In order to make the configuration, features, and effectiveness of the present invention more understandable and appreciated, the present invention will be described in detail below with reference to the embodiments.

[0029] In order to solve the above problems of the prior art, the present invention provides a method and structure for producing a conductive material with a larger specific surface area, the method includes the steps of forming a block layer on the outer surface of a precursor support, rolling to crack a part of the outer surface of the block layer, so as to form a crack gap to expose a part of the outer surface of the precursor support, and adding a conductive material to electrically connect to the part of the precursor support, so as to produce a conductive material with a larger specific surface area, which can meet the needs of materials with a larger specific surface area in industrial applications.

[0030] Please refer to Fig. 1, which is a flow chart of a material manufacturing method according to an embodiment of the present invention. As shown in Fig. 1, the present embodiment provides a method for manufacturing a conductive material with a larger specific surface area, which includes the following steps:

[0031] Step S02: To prepare a mixed precursor, a block layer is formed on the outer surface of a support precursor.

[0032] Step S04: The mixed precursor is rolled to crack a part of an outer surface of the block layer to form a plurality of crack gaps, and a part of an outer surface of the support precursor is exposed through the plurality of crack gaps.

[0033] Step S06: Add a conductive material to the mixed precursor so that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps, thereby producing a conductive material with a larger specific surface area.

[0034] Please refer to FIG. 1 again. Also, FIGS. 2A to 2D are schematic diagrams of a material structure according to an embodiment of the present invention. As shown in FIGS. 2A to 2B, in step S02 of the present embodiment, a block layer 14 is formed on the outer surface of the support precursor 12. That is, the block layer 14 covers the outer surface of the support precursor 12 to produce a mixed precursor 16. The block layer 14 can prevent the surface area of ​​the support precursor 12 from being reduced due to the fibers in the support precursor 12 being entangled, crushed, or bonded to each other.

[0035] According to one embodiment, the support precursor 12 comprises carbon nanotubes (CNTs) or nanometer metal fibers. The metal of the nanometer metal fibers may be copper, silver or nickel, although the invention is not limited to this embodiment.

[0036] According to one embodiment, any one of hydrothermal synthesis, electroless plating, electroplating, physical vapor deposition (PVD), chemical vapor deposition (CVD), or a combination of any of the above methods may be adopted to form the blocking layer 14 on the outer surface of the support precursor 12. However, the present invention is not limited to this embodiment.

[0037] Please refer to Figure 1 and Figures 2A to 2D again. As shown in the figures, in step S04 of this embodiment, after forming the mixed precursor 16 using the previous steps, the mixed precursor 16 is rolled to apply force to the mixed precursor 16. As a result, the mixed precursor 16 and the support precursor 12 in the block layer 14 are bent and deformed, cracks are generated in the outer surface of the block layer 14, and multiple crack gaps 142 are generated in the outer surface of a part of the block layer 14, and as a result, parts of the outer surface of the support precursor 12 are exposed in the multiple crack gaps 142.

[0038] According to this embodiment, a plurality of crack gaps 142 are formed and exposed by deforming and restoring the block layer 14 .

[0039] Please refer to Figure 1 and Figures 2A to 2D again. As shown in the figures, in step S06 of this embodiment, a conductive material 18 is added to the mixed precursor 16, and the conductive material 18 contacts and is electrically connected to the support precursor 12 through a plurality of crack gaps 142. Since the conductive material 18 is electrically connected to the support precursor 12 in the block layer 14, the surface area of ​​the support precursor 12 in contact with the outside can be increased, thereby producing a conductive material having a larger specific surface area.

[0040] According to the present embodiment, the conductive material 18 is a metallic conductive gel. The conductive material 18 is further interconnected with each other, and the fibers of the support precursor 12 are interconnected with each other, thereby providing a conductive material having a larger specific surface area.

[0041] The method for manufacturing a conductive material having a larger specific surface area according to the present embodiment can manufacture a conductive material having a larger specific surface area, and is applicable to different industries such as catalyst materials and super capacitors.

[0042] Please refer to Figure 3, which shows a flow chart of a method for manufacturing a capacitor material according to an embodiment of the present invention. As shown, this embodiment is based on the above-mentioned embodiment. This embodiment is used in a method for manufacturing a capacitor material, which includes the following steps:

[0043] Step S11: Add the support precursor to the titanium tetrachloride solution and heat it at a first temperature for a first time to form a block layer on the outer surface of the support precursor to prepare a mixed precursor.

[0044] Step S13: The mixed precursor is washed and dried.

[0045] Step S15: The mixed precursor is added to a barium acetate solution and heated at a second temperature for a second time, so that the barium acetate in the barium acetate solution reacts with the titanium oxide in the block layer to form barium titanate.

[0046] Step S17: The mixed precursor is washed and dried.

[0047] Step S19: The barium titanate particles, the conductive gel, and the mixed precursor are added to the polyvinyl butyral solution, and the block layer is cracked by rolling and mixing to generate a plurality of crack gaps, and the conductive gel and the barium titanate particles are filled into the plurality of crack gaps. The barium titanate particles contact and are electrically connected to the support precursor through the plurality of crack gaps, thereby producing a conductor material with a larger specific surface area.

[0048] Please refer to Fig. 3 again. As shown in the figure, in step S11 of this embodiment, the support precursor is added into the titanium tetrachloride solution, and then the support precursor and the titanium tetrachloride solution are mixed and heated at a first temperature. After heating for a first hour, the titanium tetrachloride solution reacts with oxygen to form titanium oxide on the outer surface of the support precursor, thereby forming a blocking layer and producing a mixed precursor.

[0049] According to this embodiment, carbon nanotubes (CNTs) are employed as the support precursor. The support precursor includes a plurality of carbon nanotubes. The plurality of carbon nanotubes, an acidic solution, and titanium tetrachloride are uniformly mixed and heated to form a first mixture. The acidic solution softens the carbon nanotubes and increases their surface activity, thereby allowing titanium to adhere to the surface of the carbon nanotubes.

[0050] According to this embodiment, the support precursor may be a nanometer metal fiber formed by a plurality of nanometer metal filaments made of nanometer metal such as copper, silver, or nickel. In addition, a plurality of nanometer metal fibers, an acidic solution, and titanium tetrachloride are uniformly mixed and heated to form a first mixture. The acidic solution enhances the surface activity of the nanometer metal, allowing titanium to adhere to the surface of the nanometer metal fiber.

[0051] According to one embodiment, the support precursor may be first washed with an acid solution to remove impurities on the outer surface of the support precursor. The acid solution may be, but is not limited to, nitric acid. Different acid solutions may be used depending on the material of the support precursor.

[0052] According to this embodiment, titanium tetrachloride (TiCl4) is used to generate intermediates of titanium oxide and its compounds.

[0053] According to this embodiment, the first temperature and the first time vary depending on the material properties of the support precursor and the titanium tetrachloride solution. For example, in the embodiment of carbon nanotubes and titanium tetrachloride, the first temperature is 80°C to 100°C and the first time is 0.5 to 10 hours. For example, the mixture of the support precursor and the titanium tetrachloride solution is heated at 90°C for 0.5 to 10 hours.

[0054] According to an embodiment, the mixture of the acid solution, the support precursor, and titanium tetrachloride may be vibrated in an ultrasonic vibrator for 1 to 2 hours to achieve uniform mixing.

[0055] Please refer to Fig. 3 again. As shown in the figure, in step S13 of this embodiment, the mixed precursor is further washed with deionized water and ethanol so that the pH value is neutral. For example, hydrochloric acid generated during the reaction of producing titanium oxide from titanium tetrachloride is removed. Then, the mixed precursor is dried using an oven.

[0056] In the above embodiment of carbon nanotubes and titanium tetrachloride, the mixed precursor is a titanium oxide-carbon nanotube (TiO2-CNT) precursor.

[0057] According to this embodiment, the mixed precursor is dried at 50°C to 70°C.

[0058] Please refer to Figure 3 again. As shown, in step S15 of the present embodiment, the mixed precursor is added to a barium acetate solution and heated at a second temperature for a second time, so that the barium acetate in the barium acetate solution reacts with the titanium oxide in the blocking layer to form barium titanate.

[0059] According to the present embodiment, the second temperature and the second time vary depending on the material properties of the barium acetate solution and the mixed precursor. For example, in the embodiment of the barium acetate solution and the mixed precursor, the second temperature is 150°C to 170°C and the second time is 0.5 to 10 hours. For example, the mixture of the barium acetate solution and the mixed precursor may be heated at 160°C for 0.5 to 10 hours to ensure complete reaction of the mixed precursor and the barium acetate solution.

[0060] According to one embodiment, the mixture of barium acetate solution and mixed precursors may be vibrated in an ultrasonic vibrator for 1-2 hours to achieve uniform mixing.

[0061] According to one embodiment, the mixed precursor may be further washed with deionized water and ethanol to ensure that the pH value is neutral.

[0062] Please refer to Figure 3 again. As shown, in step S17 of this embodiment, the mixed precursor is dried using an oven.

[0063] In the above embodiment of the barium acetate solution and mixed precursor, the reaction of the barium acetate solution with the mixed precursor produces a barium titanate-carbon nanotube (BaTiO3-CNT) precursor.

[0064] According to this embodiment, the mixed precursor is dried at 50°C to 70°C.

[0065] Please refer to FIG. 3 again. As shown, in step S19 of this embodiment, the conductor material includes polyvinyl butyral solution, conductive gel, and barium titanate particles. The barium titanate particles, conductive gel, and mixed precursor are added to the polyvinyl butyral solution. The block layer is slightly cracked by rolling and mixing to form multiple crack gaps. The conductive gel particles fill the multiple crack gaps of the block layer of the mixed precursor, as shown in FIG. 2D. This allows the conductive fibers (carbon nanotubes in this embodiment) to contact and electrically connect to the outer surface of the support precursor through the multiple crack gaps, producing a conductor material with a larger specific surface area.

[0066] According to this embodiment, the polyvinyl butyral solution includes polyvinyl butyral (PVB), toluene (C7H8) and ethanol (CH3CH2OH). C7H8 and CH3CH2OH form a solution with a volume ratio of 3:2. PVB is added to this solution to obtain a polyvinyl butyral solution.

[0067] Please refer to Fig. 4, which shows a flow chart of the application according to one embodiment of the present invention. As shown, after the steps of adding conductive material to the mixed precursor and rolling and mixing the conductive material to contact and electrically connect with the support precursor through a plurality of crack gaps to produce a conductive material with a larger specific surface area, the method further includes the following steps:

[0068] Step S22: Coat a conductive material having a larger specific surface area on the substrate, and heat it to a sintering temperature.

[0069] Step S24: The capacitor is formed.

[0070] Please refer to Figure 4 again. As shown, in step S22 of this embodiment, a conductive material with a larger specific surface area is coated on the substrate 10.

[0071] Please refer to Figure 4 again. As shown, in step S24 of this embodiment, a conductive material with a larger specific surface area is coated under the substrate 10. After heating to a sintering temperature, a capacitor is formed.

[0072] Please refer to FIG. 5, which shows a schematic diagram of a capacitor structure according to one embodiment of the present invention. As shown, this embodiment discloses an application to the manufacture of a capacitor. According to this embodiment, a viscometer is used to test the mixed precursor. When a suitable viscosity is reached, the mixed precursor is rolled and mixed to slightly break the outer block layer of the support precursor to form multiple crack gaps.

[0073] According to one embodiment, a triple roll mill is used to roll and mix the capacitor slurry. ) will be adopted.

[0074] Please refer to FIG. 5 again. As shown in the figure, according to this embodiment, the upper and lower surfaces of the substrate 10 are coated with a capacitor slurry. The capacitor slurry is applied to the upper surface of the substrate 10 to form a first large specific surface area conductive slurry layer 20. The capacitor slurry is applied to the bottom surface of the substrate 10 to form a second large specific surface area conductive slurry layer 30. The substrate 10, the first large specific surface area conductive slurry layer 20, and the second large specific surface area conductive slurry layer 30 are the capacitor precursors. After sintering at high temperature, a capacitor product is manufactured.

[0075] According to this embodiment, the substrate 10 is a barium titanate or metal oxide ceramic substrate, for example a substrate containing barium or other dielectric material, for use in bonding with a large surface area conductive slurry.

[0076] According to this embodiment, the first large specific surface area conductive slurry layer 20 includes a plurality of first support precursors 22, a first block layer 23, and a plurality of first particles 24. According to one embodiment, the plurality of first support precursors 22 are carbon nanotubes (CNTs). The plurality of first support precursors 22 cover the first block layer 23, for example, barium titanate (BaTiO3). The plurality of first particles 24 are metal particles of the conductive slurry. However, the present invention is not limited to the embodiment.

[0077] According to this embodiment, the second large specific surface area conductive slurry layer 30 includes a plurality of second support precursors 32, a second block layer 33, and a plurality of second particles 34. According to one embodiment, the plurality of second support precursors 32 are carbon nanotubes (CNTs). The plurality of second support precursors 32 cover the second block layer 33, for example, barium titanate (BaTiO3). The plurality of second particles 34 are metal particles of the conductive slurry. However, the present invention is not limited to the embodiment.

[0078] Please refer again to Figure 5. As shown, according to this embodiment, the intermediate product is heated to a third temperature, which is the sintering temperature of the second mixture and the substrate 10.

[0079] In the above embodiment of barium titanate-carbon nanotubes (BaTiO3-CNT), the third temperature is 1000° C. to 1350° C. The intermediate product is first heated at 240° C. to 260° C. for 2 to 2.5 hours, and then further heated at 1000° C. to 1350° C. for 2 to 2.5 hours.

[0080] An object of the present invention is to provide a method and structure for producing a conductive material having a larger specific surface area, the method including the steps of forming a block layer on an outer surface of a precursor support, rolling and cracking a part of the outer surface of the block layer to expose a part of the outer surface of the precursor support, and adding a conductive material that is electrically connected to the part of the precursor support to produce a conductive material having a larger specific surface area.

[0081] Therefore, the present invention meets the legal requirements by its novelty, non-obviousness, and usefulness. However, the above description is merely an embodiment of the present invention, and is not used to limit the scope and scope of the present invention. Any equivalent changes or modifications made according to the shape, structure, features, or spirit of the present invention are included in the appended claims of the present invention.

Claims

1. A method for producing a conductive material having a larger specific surface area, comprising the steps of: forming a block layer on an outer surface of a support precursor to produce a mixed precursor; rolling the mixed precursor to crack a portion of an outer surface of the block layer to form a plurality of crack gaps, exposing a portion of an outer surface of the support precursor through the plurality of crack gaps; and adding a conductive material to the mixed precursor such that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps, thereby producing a conductive material having a larger specific surface area.

2. 2. The method according to claim 1, wherein in the step of forming a block layer on the outer surface of a support precursor to produce the mixed precursor, the support precursor is added to a titanium tetrachloride solution to produce the mixed precursor and form a block layer on the outer surface of the support precursor.

3. To produce the mixed precursor, a step of forming a block layer on an outer surface of a support precursor, 3. The method of claim 2, wherein the mixed precursor is added to a barium acetate solution, and the barium acetate in the barium acetate solution reacts with the titanium oxide in the blocking layer to form barium titanate.

4. In a step of adding a conductive material to the mixed precursor so that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps, to produce a conductive material having a larger specific surface area, the conductive material includes a polyvinyl butyral solution, a conductive gel, and barium titanate particles, and during rolling, the block layer is cracked to form a plurality of crack gaps; The manufacturing method according to claim 3, wherein the conductive gel and the barium titanate particles contact and are electrically connected to the support precursor through the multiple crack gaps, producing a conductor material having the larger specific surface area.

5. After the step of adding a conductive material to the mixed precursor so that the conductive material contacts and is electrically connected to the support precursor through a plurality of crack gaps, and producing a conductive material having a larger specific surface area, further coating the conductive material having the larger specific surface area on the upper and lower surfaces of the substrate and heating to a sintering temperature; and forming a capacitor.

6. The method of claim 1 or 4, wherein the support precursor comprises carbon nanotubes (CNTs) or nanometric metal fibers.

7. The polyvinyl butyral solution contains polyvinyl butyral (PVB) as an adhesive or solvent, toluene (C 7 H 8 ) and ethanol (CH 3 CH 2 5. The method of claim 4, further comprising:

8. To produce a mixed precursor, a step of forming a block layer on an outer surface of a support precursor, The manufacturing method according to claim 1, wherein the blocking layer is formed on the outer surface of the support precursor by using any one of a hydrothermal synthesis method, an electroless plating method, an electroplating method, a physical vapor deposition method (PVD), a chemical vapor deposition method (CVD), or a combination of any of the above methods.

9. The method according to claim 5, wherein the sintering temperature is from 1000°C to 1350°C.

10. A structure of a conductive material having a larger specific surface area, The structure includes a substrate and a first large surface area conductive slurry layer disposed on the substrate; the first large surface area conductive slurry layer includes a first support precursor, a first block layer, and a plurality of first particles; A structure of a conductive material, characterized in that the first block layer covers the first support precursor, the first block layer includes a plurality of first crack gaps, and the plurality of first particles are arranged corresponding to the plurality of first crack gaps.

11. further comprising a second large surface area conductive slurry layer disposed beneath the substrate; the second large surface area conductive slurry layer includes a second support precursor, a second block layer, and a plurality of second particles; The conductive material structure of claim 10, wherein the second block layer covers the second support precursor, the second block layer includes a plurality of second crack gaps, and the plurality of second particles are arranged corresponding to the plurality of second crack gaps.

12. 12. The structure of conductive material according to claim 10 or 11, characterized in that the first support precursor comprises carbon nanotubes (CNTs) or nanometric metal fibers.

13. 12. The conductive material structure of claim 10 or 11, wherein the first and second blocking layers are barium titanate.

14. 12. The structure of a conductive material according to claim 10 or 11, wherein the first particles and the second particles are metal particles.

Citation Information

Patent Citations

  • Hybrid Capacitor

    JP2015519742A

  • Method and apparatus for manufacturing electrode

    JP2017183438A